Pembaruan pada Trauma Ortopedi - Wiria Aryanta MD (Fakultas Kedokteran Universitas Sriwijaya, 2019)
Orthopedic trauma is a broad term describing all kinds of injuries affecting the bones, joints, muscles, tendons, and ligaments in any part of the body that are caused by trauma. The term is wide-ranging and may refer to minor fractures or severely broken bones with a direct threat to the patient’s life. Orthopaedic surgeries focused on treating fractured bones and making sure the injured part of the body regains its original strength and maximum function it used to have prior to the injury. The many different types of orthopedic trauma are classified based on the affected body part: Upper extremity injury, which includes a broken arm or wrist, collarbone, or ribs; Lower extremity injury, which includes a broken ankle, hip, or legs; Soft tissue injury, which affects the muscles, tendon, and ligaments.Orthopedic trauma is treated depending on its severity. Those who have minor injuries such as fractures can be easily treated by general orthopedists, although in some cases, the expertise of subspecialists may become necessary. Orthopedic trauma uses both surgical and non-surgical techniques to treat the affected bones and soft tissues. Minor fractures and dislocations of specific bones such as the scapula, humerus, and clavicle, among others, can be treated non-surgically through an external fixation method. This means that orthopedic devices such as casts, braces, and splints are placed outside the body to keep the injured part stable during the recovery period. Surgical means, on the other hand, include:Minimally invasive surgery; Conventional surgery; Internal fixation method; Bone grafting and bone/ joint transplantation; Limb lengthening; Lower limb reconstruction; Upper limb reconstruction; Soft tissue reconstruction; Tendon & nerve reconstruction. The search for the optimal treatment techniques in orthopaedic still on going up until now, including new techniques, approach, mode of fixation, implant components, and also rehabilitation protocols.